Turkey : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that the Turkish economy achieved a welcome reduction of imbalances in 2012. In 2013, growth has accelerated significantly on the back of a monetary and fiscal policy stimulus. The economy is projected to expand by 3.8 percent this year, with private consumption and public investment as the main contributors. With this rotation back to domestic demand-led growth, the current account deficit is widening again, while inflation remains above target. The authorities are on track to meet their 2013 budget targets, despite rapid spending growth. Executive Directors have expressed satisfaction that the Turkish financial system is generally sound.